Tropane alkaloids and terpenes synthase genes of Datura stramonium (Solanaceae) - Sabina Velázquez-Márquez; Iván M. De-la-Cruz; Rosalinda Tapia-López; Juan Núñez-Farfán (PeerJ, 2021)
Background Plants have evolved physical–chemical defense to prevent/diminish damage by their enemies. Chemical defense involves the synthesis’ pathways of specialized toxic, repellent, or anti-nutritive metabolites to herbivores. Molecular evolutionary studies have revealed the origin of new genes, acquisition and functional diversification along time in different plant lineages. Methods Using bioinformatic tools we analyze gene divergence of tropane alkaloids (TAs) and terpene synthases (TPSs) in Datura stramonium and other species of Solanaceae; compared gene and amino acids sequence of TAs and TPSs on genomes, cDNA and proteins sequences of Viridiplantae. We analyzed two recently assembled genomes of D. stramonium (Ticumán and Teotihuacán), transcriptomes of Datura metel and genomes of other Solanaceae. Hence, we analyzed variation of TAs and TPSs to infer genes involved in plant defense and plant responses before stress. We analyzed protein modeling and molecular docking to predict interactions between H6H and ligand; we translated the sequences (Teo19488, Tic8550 and Tic8549) obtained from the two genomes of D. stramonium by using Swiss-Model and Ramachandran plot and MolProbity structure validation of Teo19488 protein model. Results For TAs, we detected an expansion event in the tropinone reductase II (TRII) and the ratio synonymous/non-synonymous substitutions indicate positive selection. In contrast, a contraction event and negative selection was detected in tropinone reductase I (TRI). In Hy-oscyamine 6 b-hydroxylase (H6H), enzyme involved in the production of tropane alkaloids atropine and scopolamine, the synonymous/non-synonymous substitution ratio in its dominion indicates positive selection. For terpenes (TPS), we found 18 DsTPS in D. stramomiun and seven in D. metel; evolutionary analyses detected positive selection in TPS10.1 and TPS10.2 of D. stramonium and D. metel. Comparison of copies of TPSs in D. stramonium detected variation among them in the binding site. Duplication events and differentiation of TAs and TPSs of D. stramonium, as compared to other Solanaceae, suggest their possible involvement on adaptive evolution of defense to herbivores. Protein modeling and docking show that the three protein structures obtained of DsH6H from Teo19488, Tic-8550 and Tic8549 maintain the same interactions and the union site of 2OG-FeII_Oxy with the Hy-o ligand as in 6TTM of D. metel. Conclusion Our results indicate differences in the number of gene copies involved in the synthesis of tropane alkaloids, between the genomes of D. stramonium from two Mexican populations. More copies of genes related to the synthesis of tropane alkaloids (TRI, TRII, H6H, PMT) are found in D. stramonium as compared to Viridiplantae. Likewise, for terpene synthases (TPS), TPS-10 is duplicated in D. stramonium and D. metel. Further studies should be directed to experimentally assess gain (overexpression) or loss (silencing) of function of duplicated genes.